An Analysis of Citizens’ Participation in Governance in Sri Lanka - Nanayakkara, E.T.C. (University of Colombo, 2024)
This article explores the impact of the Right to Information Act, Personal Data Protection Act, and Online Safety Act of Sri Lanka, respectively enacted in 2016, 2022, and 2024, on citizen’s participation in governance. Although the laws serve different purposes according to their respective preambles, they purport to safeguard citizens’ ability to participate meaningfully in public life, to safeguard their personal data and overall safety in the online space. Through a qualitative analysis of primary and secondary sources, including where possible, political developments that led to the enactment of the respective Acts, this article draws two main conclusions. First, through a textual interpretation of the Acts, the implementation of the Right to Information Act, and relevant constitutional provisions, the article observes that while these legislative enactments promise robust citizen participation in governance, they undermine it by allowing compromises in privacy, information self-determination, and online speech. Secondly, although the three Acts may be theoretically reconcilable, the complex web of legislation creates contradictions, raising concerns about the meaningful implementation of any of these laws. This article excludes certain other laws that may have an impact on citizens’ ...
Keywords: Right to Information; Personal Data Protection; Online Safety; Sri Lanka